Energy performance analysis: An exploratory study of HVAC systems in efficient management of data centres - Kiruthika M; Ebin Horisson; Surya Raj Kumar (International Journal of Environmental Planning and Development Architecture, 2023)
Data center growth is being driven by the rapid proliferation of cloud services. Data centers are using an increasing amount of energy. The network is severely impacted by server workloads, cooling, and supporting equipment. The study aims to identify the energy consumption involved in building services and their operations and analyze the ways in efficient management of performance in data center. The objective of the study is to identify the critical components in building services based on energy consumptions and list the need of MEP services in the data centers and its requirements, design, operations, and challenges in the structure. This study examines that however much energy is consumed by data center services and suggests efficient methods for reducing the increased energy use of renewable resources. Furthermore, it explains how mechanical, electrical, and fire and safety system designs should function for data centres to function effectively. The document discusses industry standards for effectively planning, implementing, and evaluating the upgrading of the data center's MEP infrastructure components. The paper focuses on energy performance analysis on HVAC systems and their working procedures, environmental controls and energy consumed by systems, efficiency of equipment’s and simulate the changes proposed for increasing the efficiency of data centres.
Keywords: Cooling systems; Data Centre; Energy optimization; Operations; Simulation